Reduction of suture associated inflammation after 28 days using novel biocompatible pseudoprotein poly(ester amide) biomaterials. Issue 2 (11th June 2014) - Hernandez, Karina A.; Hooper, Rachel Campbell; Boyko, Tatiana; Golas, Alyssa R.; van Harten, Michel; Wu, D.Q.; Weinstein, Andrew; Chu, C.C.; Spector, Jason A.
Abstract Sutures elicit an inflammatory response, which may impede the healing process and result in wound complications. We recently reported a novel family of biocompatible, biodegradable polymers, amino acid‐based poly(ester amide)s (AA‐PEA), which we have shown to significantly attenuate the foreign body inflammatory response in vitro. Two types of AA‐PEA (Phe‐PEA and Arg‐Phe‐PEA) were used to coat silk or plain‐gut sutures, which were implanted in the gluteus muscle of C57BL/6 mice, while the uncoated control sutures were implanted in the contralateral side. After 3, 7, 14, and 28 days the mean area of inflammation surrounding the sutures was compared. Phe‐PEA coating of silk sutures significantly decreased inflammation compared with noncoated controls (67.8 ± 17.4% after 3d [p = 0.0014], 51.6 ± 7.2% after 7d [p < 0.001], and 37.3 ± 8.3% after 28d [p = 0.0001]) when assessed via analysis of photomicrographs using digital image software. Phe‐PEA coated plain‐gut sutures were similarly assessed and demonstrated a significant decrease in the mean area of inflammation across all time points (54.1 ± 8.3% after 3 d, 41.4 ± 3.9% after 7 d, 71.5 ± 8.1% after 14 d, 78.4 ± 8.5%, and after 28 d [all p < 0.0001]). Arg‐Phe‐PEA coated silk demonstrated significantly less inflammation compared to noncoated controls (61.3 ± 9.4% after 3 d, 44.7 ± 4.7% after 7 d, 19.6 ± 8%, and 38.3 ± 6.8% after 28 d [all p < 0.0001]), as did coated plain‐gut (37.4 ± 8.3% after 3 d [p = 0.0004], 55.0 ± 7.8% after 7 d [p < 0.0001], 46.0 ± 4.6% after 14 d [p < 0.0001], and 59.0 ± 7.9% after 28 d [p < 0.0001]). Both Phe‐PEA and Arg‐Phe‐PEA coatings significantly decrease the inflammatory response to sutures in vivo for up to 28 days. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 457–463, 2015.